Hepatic Artery Aneurysm in Granulomatosis with Polyangiitis - Sora S. Boustany; Sammy Y. Tawk; Charbel J. Mourad; Beatrice A. Karam (Dr. Sulaiman Al Habib Medical Journal)
Large vessel involvement and arterial aneurysms are not typically encountered in Granulomatosis with Polyangiitis (GPA), which is a small vessel disease. We report the case of a 70-year-old male presenting with a ruptured hepatic artery aneurysm and elevated Antineutrophil Cytoplasmic Autoantibody, Cytoplasmic (c-ANCA) titer, 9 months after the diagnosis of GPA, while on maintenance therapy with rituximab. The liver aneurysm was successfully treated with coiling and reintroduction of prednisone. Large and medium vessel aneurysms can be seen in the context of GPA, which warrants a low threshold for screening and prompt intervention to prevent life-threatening rupture.